Preliminary analysis and applications of the Indian Ocean wave drifter program - Remya, P. G.; Suresh Kumar, N.; Mithun, Sundhar B.; Praveen Kumar, B.; Anoop, T. R.; Reddem, Venkat Shesu; Jeyakumar, C.; Lotliker, Aneesh A.; Rao, E. Pattabhi Rama; Nair, T. M. Balakrishnan (Frontiers in Marine Science, 2025)
The Southern Ocean (SO) is a critical driver of global wave dynamics, generating long-period swells that propagate vast distances and significantly impact far distant coastal regions, including the Indian coastal regions. Climate change has intensified westerly winds and altered storm tracks in the Southern Hemisphere, resulting in higher wave heights and longer periods, which in turn increase the risk to coastal regions.​ However, the remote and harsh environment in the SO has historically limited in-situ wave observations, hindering a comprehensive understanding of the wave characteristics in the region. To bridge this gap, the Indian National Centre for Ocean Information Services (INCOIS) launched the Indian Ocean Wave Drifter (IOWD) program in 2021 under the Deep Ocean Mission to address the in-situ data gap in the Southern Indian Ocean. Through the deployment of GPS-enabled directional wave spectra drifters, the program has enabled near-real-time observations of wave characteristics across the SO. This article highlights the early outcomes of the IOWD program, including wave model validation, Stokes drift estimation, and swell tracking. The study emphasizes the importance of sustained in-situ observations from remote oceans for improving wave forecasting, enhancing coastal preparedness, and advancing scientific understanding of wave–current interactions and climate variability in the Indian Ocean region.